Prior hysterectomy and discomfort during colonoscopy: a retrospective cohort analysis - Dyson, Jessica K.; Mason, James M.; Rutter, Matthew D. (Endoscopy, 2014)
Background and study aims: Discomfort during colonoscopy may affect acceptability of the procedure. The study aim was to determine factors, including prior hysterectomy and gender, associated with higher levels of patient discomfort during colonoscopy to help with procedural planning such as choice of instrument and sedation.Methods: A retrospective cohort study of colonoscopies (n = 1098) performed between February 2007 and March 2012 at the Tees Bowel Cancer Screening Centre within the English Bowel Cancer Screening Programme (BCSP). Determinants of moderate/severe discomfort assessed using the Gloucester Scale were explored, using logistic regression with a range of participant and procedural variables.Results: Rates of moderate/severe discomfort varied significantly among men, women without hysterectomy, and women with hysterectomy (5.8 %, 10.4 %, and 17.8 %, respectively; P < 0.001). In an unadjusted model, women with hysterectomy were significantly more likely to experience moderate/severe discomfort than those without (odds ratio [OR]1.87, 95 % confidence interval [95 %CI] 1.05 – 3.32, P = 0.005). The very strong influence of sedation on discomfort level precluded an adjusted model. In subgroup analysis of participants receiving sedation, adjusted comparison again showed increased odds for moderate/severe discomfort for women with hysterectomy, compared with women without (OR 1.70, 95 %CI 1.03 – 2.80, P = 0.036).Conclusions: Prior hysterectomy is associated with greater levels of moderate/severe discomfort in women undergoing colonoscopy. Minimizing participant discomfort is desirable in any screening or surveillance program. This should be considered in preprocedural counseling and in selecting equipment, sedation, and analgesia. Further studies should examine methods to minimize discomfort in those with prior hysterectomy.